xCP peer-to-peer content protection. - Pestoni, F. (IEEE Signal processing magazine)
In this article, we present a new protocol for implementing an authorized domain, a collection of devices that are equally authorized to play content. This is a new direction for content protection schemes that represents a careful balance between the needs and wants of consumers and content owners. Our protocol is a novel application of cryptographic technique known as broadcast encryption in a configuration that had not been explored previously: a peer-to-peer (P2P) network. We discuss the details of a P2P protocol based on broadcast encryption that supports and enforces renewable content protection for home networks. Several technical advantages of this protocol, including lower computational requirements, flexible network topology and support for intermittently connected devices, are given.